INCRETIN-BASED THERAPIES FOR OBESITY MANAGEMENT: THE IMPACT OF PATIENT EDUCATION AND LIFESTYLE MODIFICATION ON LONG-TERM TREATMENT OUTCOMES - Natalia Senatorska; Katarzyna Kleszczewska; Agnieszka Pruska; Julia Rarok; Daria Godlewska; Hanna Pietruszewska; Monika Banaszek; Agata Panfil; Julia Błocka; Agata Lurka (International Journal of Innovative Technologies in Social Science, 2025)
Obesity represents one of the most pressing global health challenges, driven by complex biological, behavioral, and environmental factors. Incretin-based pharmacotherapies, such as GLP-1 receptor agonists and dual GLP-1/GIP receptor agonists, have redefined the clinical approach to obesity management by enabling substantial and sustained weight reduction. However, long-term treatment success extends beyond pharmacological efficacy alone. This review examines the role of patient education and lifestyle modification as critical determinants of adherence, behavioral change, and sustainability of weight loss during incretin therapy. Integrating pharmacotherapy with structured education, digital coaching, and telehealth-based interventions enhances motivation, reduces treatment fatigue, and promotes lasting metabolic improvement. The interdisciplinary model proposed in this study positions patient empowerment and health literacy as key drivers of therapeutic success. By combining medical innovation with behavioral and social approaches, incretin therapy can evolve into a cornerstone of holistic, technology-supported chronic obesity management.